2020
DOI: 10.1242/dev.184069
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1-mediated axonal transport of CB1 receptors is required for cannabinoid-dependent axonal growth and guidance

Abstract: Endocannabinoids modulate growth cone dynamics and axonal pathfinding through the stimulation of cannabinoid type-1 receptors (CB1R) which function depends on its delivery and precise presentation at the growth cone surface. However, the mechanism involved in the axonal transport of CB1R and its role in eCB signaling remains elusive. Kinesin-1 mutations have been identified in patients with abnormal cortical development and impaired white matter integrity. We found defects in axonal pathfinding and fasciculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…The recent analysis of a mutant mice lacking the kinesin-1 light chain KLC1 has revealed hypoplasia of the internal capsule tract, that includes corticofugal and thalamocortical axons. The innervation defects were found to be caused by an impaired kinesin-1-dependent axonal transport of the cannabinoid type-1 receptors (CB1R), and the subsequent axon unresponsiveness to endocannabinoids signaling ( Saez et al, 2020 ).…”
Section: Microtubule-associated Proteins In Axon Guidancementioning
confidence: 99%
“…The recent analysis of a mutant mice lacking the kinesin-1 light chain KLC1 has revealed hypoplasia of the internal capsule tract, that includes corticofugal and thalamocortical axons. The innervation defects were found to be caused by an impaired kinesin-1-dependent axonal transport of the cannabinoid type-1 receptors (CB1R), and the subsequent axon unresponsiveness to endocannabinoids signaling ( Saez et al, 2020 ).…”
Section: Microtubule-associated Proteins In Axon Guidancementioning
confidence: 99%
“…Kinesin light chain is generally located at the end of kinesin and participates in cargo transport ( Saez et al, 2020 ). Therefore, IQD may co-localize with microtubules in addition to its classic nuclear localization, a finding subsequently confirmed using high-resolution fluorescence microscopy.…”
Section: Iqd Proteins the Scaffold Proteins Associated Microtubulesmentioning
confidence: 99%
“…Along with classical guidance cues, other signaling molecules regulate axon fasciculation in addition to their other better-known functions. Endocannabinoids, for instance, have been identified as guidance cues regulating axon pathfinding and elongation in mouse and xenopus [ 74 ], and deletion of the cannabinoid receptor CB 1 R from mouse cortical neurons in vivo causes a defasciculation of their axons [ 75 , 76 ]. A recent study reported that Kinesin-1 regulates the trafficking and sub-cellular localization of CB 1 R in mouse cortical neurons, thereby modulating endocannabinoid signaling and axon fasciculation [ 76 ].…”
Section: Axon Fasciculation and Adhesionmentioning
confidence: 99%